Odpowiedzi

2009-09-28T20:56:27+02:00
Najlepsza Odpowiedź!
2009-09-28T20:56:44+02:00
Rozwiaz rownanie:

x+2 x+3 2
------ + ---------- = ----------------
x-2 x-3 (x-2 )( x-3 )

Dziekuje :)
wspólny mianownik zał:x∈R\{2,-2,3,-3}
(x+2 )(x-3 )+(x+3 )(x-2) przez (x-2 )( x-3 )=2przez(x-2 )( x-3 )
(x+2 )(x-3 )+(x+3 )(x-2) =2
x²-3x+2x-6+x²-2x+3x-6=2
2x²-6=2
2x²=8
x²=4
x=2 lub x=-2 ale te liczby są wykluczone z dziedziny, zatem równanie nie ma rozwiązania
2009-09-28T21:44:03+02:00
(x+2 )(x-3 )+(x+3 )(x-2) =2
x^2-3x+2x-6+x^2-2x+3x-6=2
2x^2-6=2
2x²=8
x^2=4
x=2